Utilizing floodwaters for recharging depleted aquifers and sustaining irrigation: lessons from multi-scale assessments in the Ganges River Basin, India - Pavelic, Paul; Sikka, Alok; Alam, Mohammad Faiz; Sharma, Bharat R.; Muthuwatta, Lal P.; Eriyagama, Nishadi; Villholth, Karen G.; Shalsi, S.; Mishra, V. K.; Jha, S. K.; Verma, C.L.; Sharma, N.; et al. (International Water Management Institute, 2021)
Pragmatic, cost-effective, socially inclusive and scalable solutions that reduce risks from recurrent cycles of floods and droughts would greatly benefit emerging economies. One promising approach known as Underground Transfer of Floods for Irrigation (UTFI) involves recharging depleted aquifers with seasonal high flows to provide additional groundwater for irrigated agriculture during dry periods, while also mitigating floods. It has been identified that there is potential for implementing the UTFI approach across large parts of South Asia. The first pilot-scale implementation of UTFI was carried out in a rural community of the Indo-Gangetic Plain in India, and performance of the approach was assessed over three years from a technical, environmental, socioeconomic and institutional perspective. The results are promising and show that UTFI has the potential to enhance groundwater storage and control flooding, if replicated across larger scales. The challenges and opportunities for more wide-scale implementation of UTFI are identified and discussed in this report. In areas with high potential for implementation, policy makers should consider UTFI as an option when making decisions associated with relevant water-related development challenges.